2017
DOI: 10.1111/jcpp.12754
|View full text |Cite
|
Sign up to set email alerts
|

Homotypic and heterotypic continuity of symptoms of psychiatric disorders from age 4 to 10 years: a dynamic panel model

Abstract: Background: Childhood psychiatric disorders and their symptoms evince both within-disorder (homotypic) and between-disorder (heterotypic) continuities. These continuities may be due to earlier symptoms causing later symptoms or, alternatively, that the same (unknown) causes (e.g., genetics) are operating across time. Applying a novel data analytic approach, we disentangle these two explanations. Methods: Participants in a Norwegian community study were assessed biennially from 4 to 10 years of age with clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
70
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 43 publications
(51 reference statements)
15
70
0
1
Order By: Relevance
“…The majority of the available studies have focused on these links in young children. Partly consistent with our results, one such recent study (Wichstrøm et al 2017) based on a community sample of children in Norway assessed biennially from age 4 to 10 found that ADHD predicted anxiety two years later but not vice versa. In our study anxiety/depression were predictors of lower levels of ADHD symptoms at two time points during adolescence.…”
Section: Who Reportedsupporting
confidence: 92%
“…The majority of the available studies have focused on these links in young children. Partly consistent with our results, one such recent study (Wichstrøm et al 2017) based on a community sample of children in Norway assessed biennially from age 4 to 10 found that ADHD predicted anxiety two years later but not vice versa. In our study anxiety/depression were predictors of lower levels of ADHD symptoms at two time points during adolescence.…”
Section: Who Reportedsupporting
confidence: 92%
“…Widespread comorbidity (Kessler et al, 2005) coupled with shared genetic and environmental risk (Waldman, Poore, van Hulle, Rathouz, & Lahey, 2016;Wichstrøm, Belsky, & Steinsbekk, 2017) has led to a surge in models that conceptualize psychopathology as a number of broad transdiagnostic dimensions. Currently the most widely discussed model includes a general psychopathological factor, labeled p, that is purported to account for the moderate correlations between psychopathological dimensions (Caspi et al, 2014;Lahey, Krueger, Rathouz, Waldman, & Zald, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the study offers an elegant demonstration of the potential of the DPM approach for disentangling self-perpetuating (or even self-aggravating) factors from common etiology as a cause for continuity and/or comorbidity of mental health problems. The study by Wichstrøm et al (2017) undoubtedly will inspire other research. Potentially, it may hold true in other research that most continuity in symptoms is due to time-invariant factors.…”
mentioning
confidence: 88%
“…The study by Wichstrøm et al. () undoubtedly will inspire other research. Potentially, it may hold true in other research that most continuity in symptoms is due to time‐invariant factors.…”
mentioning
confidence: 92%
See 1 more Smart Citation